2010
DOI: 10.1051/0004-6361/200912978
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional structure of sunspots

Abstract: Aims. Many sunspots are surrounded by a radial outflow called the moat flow. We investigate the moat flow at two different heights of the solar atmosphere for a sunspot whose magnetic properties were reported in the first paper of this series. Methods. We use two simultaneous time series taken with the Transition Region And Coronal Explorer (TRACE) in white light and in the UV at 170 nm. The field-of-view is centered on the small sunspot NOAA 10886 located near disk center. Horizontal velocities are derived by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
1
14
2
Order By: Relevance
“…Sobotka & Roudier (2007) determined that the moat radius is independent of the spot size. However, Balthasar & Muglach (2010) found that the moat flow terminates at a distance of four times the spot radius -in contrast to three times the spot radius in the present study. Extended statistical studies will help us to clarify this issue.…”
Section: Horizontal Proper Motionscontrasting
confidence: 99%
“…Sobotka & Roudier (2007) determined that the moat radius is independent of the spot size. However, Balthasar & Muglach (2010) found that the moat flow terminates at a distance of four times the spot radius -in contrast to three times the spot radius in the present study. Extended statistical studies will help us to clarify this issue.…”
Section: Horizontal Proper Motionscontrasting
confidence: 99%
“…However, an unusual case was reported by Zuccarello et al (2009) when several moving bipolar magnetic elements were observed moving away from a sunspot without penumbra. Also, observations show that the moving magnetic elements are not passively transported by the moat flow of plasma, and they can move faster than the plasma (Balthasar and Muglach, 2010). This is consistent with the sea-serpent behavior of the magnetic-field lines in the penumbra, which also produces moving bipolar elements, as was originally suggested by Harvey and Harvey (1973).…”
Section: Figuresupporting
confidence: 84%
“…In the two-hour averaged LCT flow maps, the overall impression of flow vectors for G-band and Ca ii H images is indistinguishable. The flow patterns around the satellite sunspot are different from regular sunspots (e.g., Balthasar & Muglach 2010) because of its nonradial penumbra and location within a complex active region. The most intriguing feature in the G-band flow maps is the anticlockwise spiral motion around the dominant umbral core N3.…”
Section: Flow Fields In Photosphere and Chromospherementioning
confidence: 94%